Influence of residence time on the conversion of carbon dioxide IN a dielectric barrier discharge system - Mora-Mendoza, Eduin Yesid; Sarmiento-Santos, Armando; Casallas-Caicedo, Francy Mayoli (Universidad Pedagógica y Tecnológica de Colombia, 2020)
This paper presents a study about the importance of residence time, also called permanence time, of a gas in a gap of dielectric barrier discharge, for the treatment of carbon dioxide CO2, which is a pollutant gas. Along with CO2, hydrogen H2 is added to form the atmosphere of the discharge reaction. It was studied the behavior of power deliver to system as a function of operation voltage using alumina and quartz as dielectrics. CO2 conversion was studied as a function of residence time for three different compositions of the CO2 + H2 mixture, for three different values of the active electrical power supplied to the system and for three different values of frequency of operation using alumina as dielectric. The percent conversion of CO2 in fixed working conditions was increased with increasing residence time, regardless of the composition of the mixture of the two gases, of the electrical power and the operation frequency, finding the highest values for the least amount of CO2 in the mixture, for higher power delivered and for the lower frequency of operation.